Editorial - Donato, Paulo (2018)
One year has now passed since the online submission and editing system was implemented, a further step was taken to index the main databases of medical journals. Starting with this issue, all articles published in Acta Radiológica Portuguesa will be available in English. Submission of the papers, as previously, may be done directly in English (without the Portuguese version), maintaining the possibility of submission in Portuguese. In this case, if the paper is accepted for publication, it will subsequently be translated into English by the Editorial Board of the Journal, according to the authors’ corrections. Thus, when submitting in English, the paper will be available only in that language and when submitting it in Portuguese, the two versions will be published, one in Portuguese and one in English. With this measure, we hope to maintain the national identity of the Journal and make international indexing easier. In view of the interest shown by a large number of Radiologists present at the last SPRMN Conference, the person responsible for the updating program in Mammary Imaging, Dr. José Carlos Marques, was invited for the authorship of the article of opinion in the present issue of the Journal.